Trust-repair Discourse on Facebook's Cambridge Analytica Scandal - Muhammad Arif Amran (ELITE: Journal of English Language and Literature, 2016)
This research discusses the repair of trust made by Facebook regarding the Cambridge Analytica Scandal based on the trust-repair discourse model established by Fuoli and Paradis. The objective of this research is to find out how the trust violation repaired by Mark Zuckerberg as CEO of Facebook. This research used descriptive qualitative method. The source of data in this research was taken from the discourse uploaded by Mark Zuckerberg on March 22, 2018. The data was collected through reading intensively, identifying, and classifying based on communicative action models of Fuoli and Paradis. The data was analyzed by presenting, describing, interpreting and concluding the data to answer the research question of this research. Researchers found that Mark Zuckerberg as CEO of Facebook adopted strategies such as neutralizing the negative and emphasizing the positive to improve the company's trust from three aspects, namely ability, integrity, and benevolence. Zuckerberg adopts a lot emphasize the positive strategy to improve trust from the aspect of ability. He mainly adopts the strategy of emphasizing the positive to show that they are capable in eliminating risks. Meanwhile, in terms of integrity and benevolence, Zuckerberg uses a combination of emphasize the positive and neutralize the negative strategy. By emphasizing the positive, Zuckerberg intends to build an honest image for the company. With neutralizing the negative, he tries to lessen the negative impact of the accusation. Through the use of this strategy Zuckerberg rebuilt and renegotiated the company's trust.